Symptomatic hyponatraemia associated with tolbutamide therapy. - Darlow, B. A. (BMJ Group, 1977)
A case of hyponatraemic coma occurring in a patient with diabetes mellitus treated with tolbutamide is described. Although chlorpropamide is known to cause water retention in some circumstances, this is a less well recognized complication of tolbutamide therapy.